Long noncoding RNA PTPRG‐AS1 acts as a microRNA‐194‐3p sponge to regulate radiosensitivity and metastasis of nasopharyngeal carcinoma cells via PRC1. Issue 10 (16th April 2019) - Yi, Liang; Ouyang, Lei; Wang, Shuang; Li, Shi‐Sheng; Yang, Xin‐Ming
Abstract: Protein regulator of cytokinesis 1 (PRC1) has been reported in correlation with various malignancies. Functionality of PRC1 in nasopharyngeal carcinoma (NPC) was investigated, in perspective of long noncoding RNA (lncRNA) regulatory circuitry. Aberrant expressed messenger RNA and lncRNA were screened out from the Gene Expression Omnibus microarray database. NPC cell line CNE‐2 was adopted for in vitro study and transfected with mimic or short hairpin RNA of miR‐194‐3p and PTPRG‐AS1. The radioactive sensitivity, cell viability, migration, invasion, and apoptosis were detected. PTPRG‐AS1 and PRC1 were upregulated in NPC, whereas miR‐194‐3p was downregulated. PTPRG‐AS1 was found to specifically bind to miR‐194‐3p as a competing endogenous RNA and miR‐194‐3p targets and negatively regulates PRC1. Overexpressed miR‐194‐3p or silenced PTPRG‐AS1 resulted in enhanced sensitivity to radiotherapy and cell apoptosis along with suppressed cell migration, invasion and proliferation in NPC. Furthermore, impaired tumor formation was also caused by miR‐194‐3p overexpression or PTPRG‐AS1 suppression through xenograft tumor in nude mice. In our study, PTPRG‐AS1/miR‐194‐3p/PRC1 regulatory circuitry was revealed in NPC, the mechanism of which can be of clinical significance for treatment of NPC. Abstract : In our study, PTPRG‐AS1/miR‐194‐3p/PRC1 regulatory circuitry was revealed in NPC, the mechanism of which can be of clinical significance for the treatment of NPC.